AWS Certified Solutions Architect : Associate (SAA-C02) guided cert prep : a complete path of videos, books, practice tests, and live training to help you gain exam readiness - Wilkins, Mark (Pearson IT Certification, 2022)
Level up your IT career with the knowledge required to become an Associate level AWS Certified Solutions Architect. This expert-led certification study resource provides a guided path to exam success using video from the Complete Video Course series, Cert Guide chapters, two types of quizzes, and practice tests.